PENERAPAN KONSELING KELOMPOK DENGAN PENDEKATAN BEHAVIORISTIK DALAM MENGATASI RENDAHNYA KEMANDIRIAN BELAJAR SISWA - Cantika; Suriatie, Mimi; Feronika, Nopi (Jurnal Bimbingan dan Konseling Pandohop, 2022)
The purpose of this study was to determine whether behavioristic techniques can increase student learning independence through group counseling in class VIII of SMP Isen Mulang Palangka Raya. This type of research is a quantitative study with a pre-experimental design with one group pretest-posttest type. Data were analyzed using descriptive statistics from the paired sample T-test (SPSS version 25 program). The population in this study were 11 students in class VIII with a total sample of 4 students. The results of the calculation of the average score of learning independence before participating in group counseling services with behavioristic techniques an average of 65 then after being given group counseling with behavioristic techniques increased to 86.75 with an average increase of 21.75. Then from the calculation results of the pretest and posttest values using the Paired Samples T-test is 0.003 < from 0.05, then the null hypothesis is rejected. It can be concluded that there is a significant effect from the application of group counseling with a behavioristic approach to overcome the low learning independence of students at SMP Isen Mulang Palangka Raya.